Enhancing Literacy Development in Nigeria through Reading and Writing Skills Development - Mangvwat , Solomon E.; Meshak, Victor J. (Journal of Education and Practice, 2022)
Purpose: The Purpose of this paper is to draw the attention of the Government of Nigeria to the need to support the teaching of reading and writing skills in Nigerian schools for the much-needed national development. Method and data used: The research was carried out using the library research method which furnished the relevant information on the relevance of reading and writing skills in the acquisition of literacy, which is fundamental to Nigeria's development. Finding: The goal of education in Nigeria is development. A kind of development that is human-centred and focused on the aptitude and achievements of an individual. Development is realised when there is a highly literate populace. However, this set objective is hampered by the growing rate of illiteracy. A UNESCO survey in 2015 reveals that 65 million Nigerians out of the 170 million Nigerians are illiterates. They can neither read nor write. The latest report from Varrella (2021) indicates that 62% of Nigerians are literate, even though not quite a good rate. Hence, a development that ought to be sustainable is threatened. The lukewarm attitude of the government in seeing that literacy gains prominence in the curriculum through reading and writing skills is dashed. With the poor literacy rate, it is appalling and a thing of grave concern for a nation that is focused on development through education to have more than half of its citizens as illiterates. Illiteracy is a clog in the wheel of sustainable educational development; it has placed the Nigerian state high on the global poverty index and exposed it to so many diseases and epidemics. Hence, illiteracy is linked to poverty. Unique Contribution to Theory, Practice and Policy: Furthermore, the paper found low literacy rate, inadequate funding of education and lack of professional literacy education teachers in the country and it concludes by strongly recommending the promotion of reading and writing skills through access to quality education, adequate funding of education and training of specialist teachers for the needed development of the nation, and sustain its future relevance in the comity of nations.